2018
DOI: 10.3389/fnhum.2018.00404
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Slow-Wave-Sleep Predict Acquisition of Full Cognitive Maps

Abstract: Accumulating evidence suggests that sleep, and particularly Slow-Wave-Sleep (SWS), helps the implicit and explicit extraction of regularities within memories that were encoded in a previous wake period. Sleep following training on virtual navigation was also shown to improve performance in subsequent navigation tests. Some studies propose that this sleep-effect on navigation is based on explicit recognition of landmarks; however, it is possible that SWS-dependent extraction of implicit spatiotemporal regularit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Also, it is to be noted that our results showed that the non‐REM N3 sleep stage was of a lower percentage in the PD + OSA group. Non‐REM N3 is known to be the slow‐wave sleep (SWS), 57 and the reduction of this sleep stage is associated with a higher risk of cognitive decline 58,59 . Another mechanism by which OSA may influence cognition in PD patients is via increasing the risk of certain comorbidities, including mainly hypertension and heart diseases, as better cardiovascular health was found to be directly associated with better cognitive functions 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is to be noted that our results showed that the non‐REM N3 sleep stage was of a lower percentage in the PD + OSA group. Non‐REM N3 is known to be the slow‐wave sleep (SWS), 57 and the reduction of this sleep stage is associated with a higher risk of cognitive decline 58,59 . Another mechanism by which OSA may influence cognition in PD patients is via increasing the risk of certain comorbidities, including mainly hypertension and heart diseases, as better cardiovascular health was found to be directly associated with better cognitive functions 60 .…”
Section: Discussionmentioning
confidence: 99%
“…28 , past findings concerning sleep-induced insight are often characterized by a hidden rule having a temporal structure: event X at time t predicts event Y at some time-point in the future, typically a few seconds later. This type of hidden regularities are not easily identified in real time; however, during SWS, endogenous reactivations of these experiences, occurring in a time-compressed manner 1,38 , essentially bring event X and Y closer together in time and could thus allow Hebbian mechanisms – or other activity-dependent local plasticity processes in the hippocampus – to more readily associate them directly 39,40 . These associations can potentially form the basis of conscious identification of the hidden rule by the prefrontal cortex when performing the task again the following morning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the relevance of sleep for implicitly extracting hidden rules has been described in other tasks such as extracting group hierarchies from relations within pairs (Ellenbogen, Hu, Payne, Titone, & Walker, 2007), or in spatial contexts (Lerner & Gluck, 2018). Finally, the capacity of sleep to extract abstract rules also works in probabilistic paradigms (Djonlagic et al., 2009).…”
Section: Sleep As Operating Microstructure Of the Habitusmentioning
confidence: 99%